Otros gustos, otras costumbres y otros consumos Los microempresarios frente a los megamercados - Jacinto Pazos, Pedro (2007)
The socio-cultural expressions that we observe in the supermarkets are causing a series of transformations in the reasoning of each individual as a result of the consumer forms established inside and outside of these commercial places. In other words, nowadays there are other forms of human interaction because of being commercial relationships recreating different processes and styles in the daily life of the consumers whose basic aspect is related with the culture, even in the music, the amusement and also in the different pleasures and forms of autoperceive the modern world, that the most part of micro entrepreneurs take continuously due to the massive attendance.